Management of Intra-Aortic Balloon Pumps. (June 2015) - Webb, Christopher A.-J.; Weyker, Paul D.; Flynn, Brigid C.
Intra-aortic balloon pumps (IABPs) continue to be the most widely used cardiac support devices with an annual estimate of 200 000 IABPs placed worldwide. IABPs enhance myocardial function by maximizing oxygen supply and minimizing oxygen demand. The use of IABPs is not without risk, with major vascular injury, ischemia, and infection being the most common complications, especially in high-risk patients. While recent studies have questioned the use of IABPs in patients with cardiogenic shock secondary to myocardial infarction, these studies have limitations making it difficult to formulate definitive conclusions. This review will focus on the mechanisms of counterpulsation, the management of IABPs and the evidence supporting this ventricular support therapy.